Preparation method of novel spare tire cover plate material
Patent Information
- Application Number
- CN202611404967.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-11-03
AI Technical Summary
Existing spare tire cover materials have problems during the production process, such as poor odor performance, high VOC emission, insufficient environmental protection, poor waterproof and moisture-proof performance, and easy delamination and deformation.
Low-odor white paper cores are used instead of honeycomb paper cores, and environmentally friendly adhesives such as starch glue or PVA white latex are used. Combined with plasma or corona surface activation treatment of glass fiber surface materials, the materials are bonded firmly and dimensionally accurate through high-temperature and high-pressure pressure holding and gradient cooling shaping process using hot pressing molds.
It significantly reduces VOC emissions, improves the environmental performance and rigidity of materials, ensures high dimensional accuracy and service life of products, and meets the technical requirements for low-odor automotive interiors.
Smart Images

Figure CN123025558A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of automotive interior parts technology, and in particular to a method for preparing a novel material for a spare tire cover. Background Technology
[0002] Currently, spare tire covers, as an important interior component of car trunks, primarily serve to cover the spare tire compartment, carry items, provide decoration, and reduce noise. Existing spare tire covers generally use a honeycomb paper core as the core material, with fiberglass felt and fabric laminated to the upper and lower surfaces. They are manufactured through a process of spraying polyurethane adhesive and hot-pressing. The honeycomb paper core is formed by bonding and pressing multiple layers of corrugated paper with PUR adhesive to create a honeycomb structure, which is then laminated with a fiberglass surface material and trimmed to obtain the finished product.
[0003] However, the existing technology has the following drawbacks: First, the honeycomb paper core uses chemical adhesives such as PUR glue in the production process, and the paper itself is prone to residual volatile organic compounds, resulting in poor odor performance and high VOC emission of the prepared spare tire cover, making it difficult to meet the technical requirements for low-odor automotive interiors; Second, most of the existing adhesives are chemically synthesized, containing harmful substances and having poor environmental performance, and the honeycomb paper core has strong hygroscopicity, which leads to a decrease in load-bearing capacity and insufficient waterproof performance after long-term use; Third, the bonding area between the honeycomb core layer and the surface material in the existing preparation process is limited, and local delamination is prone to occur when subjected to external forces, affecting the rigidity and service life of the product; Fourth, the existing process mostly uses single-stage cooling at room temperature in the cooling and shaping stage, and the cooling rate is difficult to control, which can easily lead to product warping and deformation, and unstable dimensional accuracy. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing a novel spare tire cover material, which solves the technical problems of existing honeycomb paper core spare tire covers, such as poor odor performance, high VOC emission, insufficient environmental protection, poor waterproof and moisture-proof properties, and easy delamination and deformation.
[0005] To achieve the above objectives, the present invention provides a method for preparing a novel spare tire cover material, comprising the following steps:
[0006] The low-odor white paper core is cut to the designed size, and the cut white paper core is subjected to flatness correction treatment to obtain the pretreated white paper core substrate.
[0007] An environmentally friendly adhesive is uniformly coated on the upper and lower surfaces of the pretreated white paper core substrate;
[0008] The glass fiber surface material undergoes surface activation pretreatment.
[0009] The white paper core substrate coated with environmentally friendly adhesive is precisely aligned and laminated with the upper and lower glass fiber surface materials to form a composite blank;
[0010] The composite blank is placed in a hot press mold for hot pressing composite molding. The hot pressing temperature, pressure and holding time are controlled to ensure that the layers are firmly bonded to obtain a semi-finished product.
[0011] The semi-finished product undergoes gradient cooling and shaping treatment;
[0012] After cooling and shaping, the semi-finished product is precisely cut and trimmed to remove excess edges and corners, forming a prototype spare tire cover that meets product specifications.
[0013] The prototype spare tire cover is subjected to odor testing and appearance quality inspection. Once it passes the inspection, the finished spare tire cover is obtained.
[0014] The step of "cutting the low-odor white paper core to the designed dimensions and performing flatness correction treatment on the cut white paper core to obtain the pretreated white paper core substrate" includes the following steps:
[0015] Unroll the low-odor white paper core roll and cut it to the designed dimensions;
[0016] Deburr and clean the edges of the cut white paper core;
[0017] The flatness of the white paper core is tested, and any parts with excessive flatness are corrected.
[0018] The corrected white paper core is left to stand and balance to eliminate internal stress, thus obtaining the pretreated white paper core substrate.
[0019] The step of "uniformly coating the upper and lower surfaces of the pretreated white paper core substrate with an environmentally friendly adhesive" includes the following steps:
[0020] Stir the environmentally friendly adhesive thoroughly and remove any bubbles;
[0021] An environmentally friendly adhesive is uniformly coated on the upper and lower surfaces of the white paper core substrate using roller coating, scraping, or spraying methods.
[0022] The coating uniformity is checked, and areas with insufficient or excessive coating are corrected to obtain the coated white paper core substrate.
[0023] The step of "surface activation pretreatment of glass fiber surface material" includes the following steps:
[0024] Clean the surface of the fiberglass material to remove dust, oil, and mold release agent residue;
[0025] The surface of the glass fiber surface material to be laminated is activated by plasma treatment or corona treatment.
[0026] To test the surface activation effect, qualified glass fiber surface material was temporarily stored in a clean environment to obtain pretreated glass fiber surface material.
[0027] The step of "precisely aligning and laminating the white paper core substrate coated with environmentally friendly adhesive with the upper and lower glass fiber surface materials to form a composite blank" includes the following steps:
[0028] Lay the lower layer of glass fiber surface material flat on the workbench with the surface-activated side facing up.
[0029] Place the coated white paper core substrate on top of the lower glass fiber surface material;
[0030] The upper glass fiber surface material is placed over the white paper core substrate, with the surface-activated side facing down.
[0031] The three layers of material are fixed and pre-pressed using a positioning fixture to remove air bubbles between the layers, resulting in a composite blank.
[0032] The step of "placing the composite blank in a hot press mold for hot pressing composite molding, controlling the hot pressing temperature, pressure and holding time to ensure that each layer is firmly bonded to obtain a semi-finished product" includes the following steps:
[0033] The composite blank is placed in the preheated hot press mold cavity;
[0034] The mold is closed and pressure is applied. The environmentally friendly adhesive is then fully cured under specified temperature and pressure conditions.
[0035] After the pressure holding period is over, slowly release the pressure, open the mold, and remove the semi-finished product.
[0036] The step of "gradient cooling and shaping of semi-finished products" includes the following steps:
[0037] The semi-finished product is transferred to the first cooling station for the first stage of cooling, so that the surface temperature is initially reduced.
[0038] The semi-finished product is transferred to the second cooling station for a second stage of cooling, which further reduces the internal temperature evenly.
[0039] The semi-finished product is transferred to a room temperature environment for the third stage of cooling and shaping to obtain the cooled and shaped semi-finished product.
[0040] This invention discloses a method for preparing a novel spare tire cover material. By replacing the traditional honeycomb paper core with a low-odor white paper core made from virgin wood pulp and processed using a special technique, and by replacing traditional PUR glue with environmentally friendly adhesives such as starch glue or PVA white latex, the invention effectively reduces the generation of volatile organic compounds and irritating odors from the material source. This significantly improves the odor level of the prepared spare tire cover and drastically reduces VOC emissions, meeting the stringent technical requirements for low-odor automotive interiors and effectively improving in-vehicle air quality and user experience. Furthermore, the environmentally friendly adhesives used do not contain harmful solvents or isocyanates, and the low-odor white paper core itself is recyclable and biodegradable, substantially improving the overall environmental performance of the product and aligning with the green manufacturing trend in the automotive industry. To further enhance product structural reliability, this invention pre-treats the glass fiber surface material with plasma or corona surface activation, significantly improving the surface energy and wettability of the glass fiber surface. This results in a stronger interfacial bond between the environmentally friendly adhesive and the glass fiber surface. Combined with the high-temperature, high-pressure pressing and composite process in the hot-pressing mold, a strong chemical bond is formed between the white paper core substrate and the upper and lower glass fiber surface materials. This effectively solves the problem of easy delamination caused by limited bonding area and insufficient interfacial bonding force in existing technologies, improving the overall rigidity and service life of the product. Regarding dimensional accuracy control, this invention corrects the flatness of the white paper core and eliminates internal stress during the substrate pre-treatment stage. After hot pressing, a three-stage gradient cooling and shaping process is used. By controlling the cooling rate, the internal and external temperatures of the semi-finished product are reduced uniformly, effectively releasing thermal stress and avoiding the warping and deformation problems easily caused by traditional single-stage room-temperature cooling. Simultaneously, CNC precision cutting and negative pressure adsorption fixing technology are used to ensure high precision in the product's dimensions and its compatibility with the vehicle's spare tire compartment. Furthermore, this invention upgrades the material system while maintaining the original molding process, eliminating the need for structural modifications to existing hot-pressing molds, laminating equipment, and cutting equipment. This significantly reduces equipment investment and production line switching costs for enterprises, demonstrating excellent industrialization potential. Regarding quality control, this invention incorporates multi-dimensional quality inspection processes at the end of the preparation process, including odor level assessment, volatile organic compound (VOC) release detection, appearance quality inspection, and mechanical property testing. This ensures that only products meeting all performance standards are accepted as finished products, effectively guaranteeing product quality stability and batch consistency. In summary, the spare tire cover prepared by this invention achieves synergistic improvements in low odor, low VOC, high environmental friendliness, high strength, and high dimensional accuracy, yielding unexpected technical benefits. Attached Figure Description
[0041] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0042] Figure 1 This is a flowchart of a method for preparing a novel spare tire cover material provided by the present invention.
[0043] Figure 2 The flowchart describes the process of cutting low-odor white paper cores to the designed dimensions and then performing flatness correction on the cut white paper cores to obtain the pre-treated white paper core substrate.
[0044] Figure 3 This is a flowchart of the process of uniformly coating the upper and lower surfaces of the pretreated white paper core substrate with an environmentally friendly adhesive.
[0045] Figure 4 This is a flowchart of the surface activation pretreatment process for glass fiber surface materials.
[0046] Figure 5 It is a flowchart of precisely aligning and laminating a white paper core substrate coated with environmentally friendly adhesive with upper and lower glass fiber surface materials to form a composite blank.
[0047] Figure 6 The flowchart describes a process of placing composite blanks in a hot press mold for hot pressing composite molding, controlling the hot pressing temperature, pressure and holding time to ensure that each layer is firmly bonded, and obtaining a semi-finished product.
[0048] Figure 7 This is a flowchart of the gradient cooling and shaping process for semi-finished products.
[0049] Figure 8 This is a flowchart of the process of precisely cutting and trimming the semi-finished product after cooling and shaping, removing excess edges and corners, and forming a prototype of the spare tire cover that meets product specifications.
[0050] Figure 9 This is a flowchart of the process of conducting odor testing and appearance quality inspection on the prototype of the spare tire cover, and obtaining the finished spare tire cover after passing the inspection. Detailed Implementation
[0051] The embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, but should not be construed as limiting the present invention.
[0052] Please see Figures 1 to 9 This invention provides a method for preparing a novel material for spare tire cover plates, comprising the following steps: S1 cuts the low-odor white paper core to the designed size and performs flatness correction treatment on the cut white paper core to obtain the pre-treated white paper core substrate. S11 unfolds the low-odor white paper core roll and cuts it to the designed dimensions; S12 performs deburring and cleaning on the edges of the cut white paper core; S13 performs a flatness test on the white paper core and corrects any parts that exceed the flatness tolerance. S14 allows the corrected white paper core to be placed in static equilibrium to eliminate internal stress, resulting in a pretreated white paper core substrate.
[0053] Specifically, the low-odor white paper core roll is unrolled from the reel and laid flat on the cutting table. The target cutting dimensions and tolerance requirements of the white paper core are determined according to the design drawings of the spare tire cover product. The white paper core is then cut along the specified dimensions using cutting equipment or die-cutting tools. During the cutting process, the speed and feed rate of the cutting tool are controlled to avoid burrs, tears, or delamination at the edges of the paper core. The cutting speed is controlled at 800 r / min to 1200 r / min, the feed rate at 0.5 m / min to 1.0 m / min, and the cutting tolerance is controlled within ±0.5 mm. After cutting, the edges are deburred using 400-600 grit sandpaper. Subsequently, a negative pressure dust extraction device (vacuum degree ≥ -0.06 MPa) is used to remove paper scraps, dust, and other impurities from the surface and edges to ensure the substrate surface is clean. The cleaned and trimmed white paper core is then placed on a flatness testing platform. A 0.05mm precision feeler gauge or laser flatness tester is used to check the flatness, with a 100mm x 100mm grid of test points to identify areas where flatness exceeds the allowable deviation. For areas with excessive flatness (local gaps > 0.3mm), a hot-press flattening machine is used at a pressure of 0.3MPa–0.5MPa and a temperature of 80℃–100℃ for 10–20 seconds. After the flatness is deemed acceptable, the white paper core is transferred to a constant temperature and humidity chamber (temperature 23℃±2℃, relative humidity 50%±5%) for horizontal equilibration for 4–6 hours. This allows the internal stress generated during cutting and correction to be fully released, preventing product deformation due to stress concentration during subsequent lamination and molding. The result is a flat, stable, and stress-free pre-treated white paper core substrate.
[0054] S2 applies an environmentally friendly adhesive evenly to the upper and lower surfaces of the pretreated white paper core substrate.
[0055] S21 involves thoroughly mixing and degassing the environmentally friendly adhesive;
[0056] S22 uses roller coating, scraping coating or spraying to uniformly coat the upper and lower surfaces of the white paper core substrate with an environmentally friendly adhesive.
[0057] S23 checks the coating uniformity and corrects areas with insufficient or excessive coating to obtain the coated white paper core substrate.
[0058] Specifically, calculate the total amount of environmentally friendly adhesive required based on the surface area of the white paper core substrate and the preset coating amount. The total coating amount of starch glue or PVA white latex is calculated as 80g / m² to 150g / m². Place the environmentally friendly adhesive in a special mixing container and stir at 200r / min to 400r / min for 15 to 20 minutes at room temperature (20℃ to 25℃) to homogenize the viscosity of the adhesive. Then connect a vacuum pump for vacuum degassing, controlling the vacuum degree at ≤-0.08MPa for 5 to 10 minutes, until there are no obvious bubbles in the adhesive solution. A micro-grooved roller coating method was used, with a roller gap of 0.10mm to 0.18mm and a coating speed of 2m / min to 4m / min. An environmentally friendly adhesive was uniformly coated onto the upper surface of the pretreated white paper core substrate, controlling the wet film thickness to be 0.08mm to 0.15mm. After flipping the substrate, the same parameters were used to uniformly coat the lower surface with the same environmentally friendly adhesive, ensuring consistent coating thickness on both surfaces. After coating, a wet film thickness gauge was used to check the coating amount on the substrate surface using a nine-square grid, with the deviation controlled within ±10%. Areas with insufficient coating (below the lower limit of 90%) were touched up with a brush, while areas with excessive coating (above the upper limit of 110%) were corrected by scraping with a scraper. After correction, the coated white paper core substrate was horizontally placed in an environment with a cleanliness level of at least Class 10,000 for 5 to 8 minutes to allow the adhesive to fully wet and initially penetrate into the interfiber spaces of the white paper core surface, resulting in the coated white paper core substrate.
[0059] S3 involves surface activation pretreatment of the glass fiber surface material; S31 cleans the surface of the glass fiber surface material, removing dust, oil, and mold release agent residue; S32 uses plasma treatment or corona treatment to activate the surface of the glass fiber surface material to be laminated. The S33 test measures the surface activation effect by temporarily storing qualified glass fiber surface material in a clean environment to obtain pretreated glass fiber surface material.
[0060] Specifically, the glass fiber surface material roll is unrolled and laid flat on the pretreatment workbench. A lint-free cloth soaked in anhydrous ethanol (analytical grade, concentration ≥99.5%) is used to wipe the glass fiber surface in the same direction, with a wiping pressure of 2 N / cm²~4 N / cm². Each piece of glass fiber is wiped 2~3 times to remove surface dust, oil, and release agent residue. After wiping, it is air-dried in a clean environment for 5min~8min. The cleaned glass fiber surface material is then sent into the plasma treatment equipment. The vacuum degree of the treatment chamber is evacuated to 10Pa~30Pa, and then a working gas (oxygen or argon, flow rate 50sccm~100sccm) is introduced. The radio frequency power is set to 300W~500W, the treatment time to 10s~30s, and the electrode spacing to 3mm~5mm. After processing, the fiberglass material is removed, and the water contact angle is measured at five randomly selected points on the fiberglass surface using a contact angle meter. The water contact angle must be ≤50°. Simultaneously, a 38mN / m dyne pen is used for line drawing, requiring the line to shrink uniformly without breakage within 2 seconds. After passing the tests, the pretreated fiberglass surface material is placed in a clean bag and sealed for temporary storage for no more than 4 hours to avoid surface activation degradation and secondary contamination. This results in a pretreated fiberglass surface material with good surface activity and a clean surface for the composite layer.
[0061] S4 precisely aligns and laminates the white paper core substrate coated with environmentally friendly adhesive with the upper and lower glass fiber surface materials to form a composite blank; S41 lays the lower glass fiber surface material flat on the worktable with the surface-activated side facing up; S42 places the coated white paper core substrate on top of the lower glass fiber surface material; S43 covers the upper glass fiber surface material on top of the white paper core substrate, with the surface-activated side facing down; S44 uses a positioning fixture to limit and fix the three layers of material and pre-press them together to remove interlayer air bubbles and obtain a composite blank.
[0062] Specifically, a 3mm-5mm thick silicone cushioning pad is laid on the stacking worktable. The lower layer of fiberglass surface material is then laid flat on the cushioning pad, with the surface-activated side facing upwards. Mechanical positioning pins (5mm-8mm in diameter, spacing matched to product dimensions) are used for initial positioning of the lower fiberglass layer, with a positioning accuracy of ±0.3mm. The white paper core substrate, coated with environmentally friendly adhesive, is then hoisted above the lower fiberglass layer. A CCD vision alignment system (resolution 1024×768 pixels or higher) is used for precise alignment, adjusting the position of the white paper core so that the edge alignment deviation with the lower fiberglass layer edge is controlled within ±0.5mm. After alignment, the upper layer of fiberglass surface material is placed over the white paper core substrate, with the surface-activated side facing downwards. Again, the CCD vision system is used to adjust the edge alignment deviation to within ±0.5mm. An aluminum alloy frame positioning fixture is used to clamp and limit the four sides of the three-layer material. The clamping force is 50 N / m to 80 N / m. After clamping, a rubber roller (Shore A 60 to 70 degrees hardness) is used for pre-pressing at a pressure of 0.5 MPa to 1.0 MPa. The pre-pressing speed is 0.2 m / s to 0.4 m / s, and the roller is reciprocated 1 to 2 times to remove interlayer air bubbles. After pre-pressing, LED transmitted light is used to check for interlayer air bubbles. Air bubbles with a diameter > 2 mm are required. After confirming that there are no air bubbles, wrinkles, or misalignments, a tightly bonded composite blank is obtained.
[0063] S5 places the composite blank in a hot press mold for hot pressing composite molding, controls the hot pressing temperature, pressure and holding time to ensure that each layer is firmly bonded, and obtains a semi-finished product; S51 places the composite blank into the preheated hot press mold cavity; S52 closes the mold and applies pressure, then performs pressure-holding composite under specified temperature and pressure conditions to fully cure the environmentally friendly adhesive; After the S53 pressure holding period ends, slowly release the pressure and open the mold to remove the semi-finished product.
[0064] Specifically, select the appropriate hot-pressing mold based on the shape of the spare tire cover product. The mold material is H13 hot work die steel, and the surface roughness Ra of the cavity is ≤0.8μm. Clean the mold cavity with acetone or anhydrous ethanol, and spray with a water-based release agent (coating amount 5g / m²~8g / m²). Install the mold on the hot press, set the hot pressing temperature to 120℃~160℃, and heat at a rate of 5℃ / min~10℃ / min for 20min~30min. Use a thermocouple to detect the mold cavity temperature, ensuring that the temperature uniformity deviation is ≤±3℃. Place the composite blank stably in the lower mold cavity, close the mold, and pressurize the hot press at a rate of 2MPa / s~4MPa / s to 6MPa~12MPa. Hold the pressure at the set temperature and pressure for 200s~350s, and control the mold temperature fluctuation within ±3℃ during the pressure holding process. After the pressure holding period, slowly depressurize to atmospheric pressure at a rate of 1MPa / s to 2MPa / s, with the depressurization time being no less than 1 / 5 of the pressure holding time. Open the mold and use a vacuum suction cup or robotic arm to smoothly remove the semi-finished product from the mold, controlling the removal time to within 10 seconds to prevent the residual heat of the mold from causing the semi-finished product to overcook.
[0065] S6 performs gradient cooling and shaping treatment on the semi-finished product; S61 transfers the semi-finished product to the first cooling station for the first stage of cooling, so that the surface temperature is initially reduced. S62 transfers the semi-finished product to the second cooling station for the second stage of cooling, so that the internal temperature is further reduced evenly. S63 transfers the semi-finished product to a room temperature environment for the third stage of cooling and shaping, resulting in a cooled and shaped semi-finished product.
[0066] Specifically, the semi-finished product removed after hot pressing is immediately transferred to the first cooling station, which is a temperature-controlled cooling platform set at 80℃~100℃. The semi-finished product is placed flat on the platform and lightly pressed with a pressure plate (pressure 0.1MPa~0.2MPa) to prevent warping. The cooling time is 30s~60s, allowing the surface temperature of the semi-finished product to drop from the hot pressing temperature to 90℃~110℃. After the first stage of cooling is completed, the semi-finished product is transferred to the second cooling station, where the platform temperature is set at 40℃~60℃. It is again placed flat and lightly pressed, and cooled for 40s~80s, allowing the overall temperature of the semi-finished product to drop to 50℃~70℃. After the second stage of cooling is completed, the semi-finished product is transferred to the third cooling station at room temperature (23℃±2℃), where it is placed horizontally on a marble platform for natural cooling and shaping. The cooling time is ≥60s, allowing the semi-finished product to completely cool to room temperature. During the cooling process, an infrared thermometer is used to check the surface temperature of the semi-finished product every 10 to 15 seconds to ensure that the actual temperature at each stage deviates from the set value by ≤ ±5℃. After the three-stage cooling is completed, a feeler gauge is used to check the warpage of the semi-finished product, which is required to be ≤ 0.2mm. After passing the test, the cooled and shaped semi-finished product is obtained.
[0067] S7 precisely cuts and trims the edges of the cooled and shaped semi-finished product, removing excess corners to form a prototype spare tire cover that meets product specifications.
[0068] S71 fixes the cooled and shaped semi-finished product onto the worktable of the cutting equipment;
[0069] S72 precisely cuts the semi-finished product according to the preset cutting path, removing excess edges and corners;
[0070] S73 performs deburring and chamfering on the cut edges to obtain the prototype of the spare tire cover.
[0071] Specifically, the cooled and shaped semi-finished product is placed flat on the CNC cutting machine's worktable, with a 5mm-8mm thick wool felt pad on the worktable surface. The vacuum adsorption system is activated, with the adsorption vacuum level set to -0.06MPa to -0.08MPa, and the adsorption area covering more than 80% of the bottom surface of the semi-finished product to ensure no displacement during the cutting process. The cutting path program for the final outer dimensions of the spare tire cover is imported into the equipment control system, with the path compensation value set to the tool radius +0.05mm. Cutting is performed using a carbide end mill or a vibrating cutter, with the spindle speed set to 8000r / min-12000r / min (end mill) or vibration frequency of 20000 times / min-30000 times / min (vibrating cutter), and the feed speed set to 1m / min-2m / min. After cutting, the cut edges are deburred using 400-600 grit sandpaper or a dedicated deburring tool to remove burrs with a height ≤0.1mm. The edges are then chamfered using a chamfering tool, with a chamfer size of R0.5mm to R1.0mm. The product's dimensions are then inspected using a coordinate measuring machine or digital caliper, with dimensional deviations controlled within ±0.3mm and diagonal length deviations ≤0.5mm. Once the inspection is passed, a preliminary spare tire cover shape is obtained.
[0072] S8 performs odor testing and appearance quality inspection on the prototype spare tire cover. Once it passes the inspection, the finished spare tire cover is obtained.
[0073] S81 assesses the odor level and detects the release of volatile organic compounds from the prototype spare tire cover.
[0074] S82 performs appearance quality inspection and mechanical performance testing on the prototype of the spare tire cover.
[0075] S83 cleans, packages, and labels the qualified products to obtain the finished spare tire cover.
[0076] Specifically, the spare tire cover prototype was placed in a standard odor testing environment at a temperature of 23℃±2℃ and a relative humidity of 50%±5%. After 24 hours to reach environmental equilibrium, 3 to 5 trained odor evaluators assessed the odor level according to the PV3900 standard. The sample was heated in an 80℃ constant temperature chamber for 2 hours and then removed. The evaluators completed the olfaction test within 30 seconds, and the average value was taken as the final odor level, which was required to be ≥6. VOC testing used the 10L Tedlar sampling bag method. The sample was placed in a sampling bag, heated at 65℃ for 2 hours, and the gas was collected. The TVOC release was analyzed using gas chromatography-mass spectrometry (GC-MS), and the TVOC was required to be ≤50μg / m³. Appearance quality inspection was conducted in a standard light source box with an illuminance of 800lx to 1000lx. The surface was checked for bubbles with a diameter >0.5mm, scratches with a length >3mm, delamination with an area >5mm², and obvious color difference. The location and number of defects were recorded. Mechanical performance testing includes: peel strength testing according to GB / T2790, tensile speed 100mm / min, requirement ≥1.5N / mm; flexural strength testing according to GB / T9341, span 64mm, indenter speed 2mm / min, requirement ≥80MPa; load performance testing with a concentrated load applied to the center of the sample, requirement ≥200N. After all the above tests are passed, surface static dust is removed using an ion fan, and the sample is sealed in a PE bag with product identification (including model, batch, production date, and inspector code) affixed before being put into storage to obtain the finished spare tire cover.
[0077] Example 1:
[0078] Low-odor white paper core with a density of 120 g / m² was selected. The cutting blade rotated at 1000 r / min, the feed speed was 0.8 m / min, and after deburring with 600-grit sandpaper, it was vacuumed under negative pressure. The flatness correction parameters were 0.4 MPa / 90℃ / 15 s, and it was allowed to stand for 5 h (23℃ / 50%RH). The starch adhesive was stirred at 300 r / min for 18 min, vacuum degassing was performed at -0.085 MPa / 8 min, the coating amount with a micro-concave roller was 110 g / m², the wet film thickness was 0.11 mm, the coating speed was 3 m / min, and it was allowed to stand for 6 min after correction. The glass fiber surface material was wiped three times with anhydrous ethanol and then treated with plasma (400 W, 20 s, O2 / 80 sccm, electrode distance 4 mm). After treatment, the water contact angle was 42°, and the dyne pen strength was 40 mN / m. During lamination, CCD vision alignment is used, with an edge deviation of ±0.3mm. The aluminum alloy clamping force is 60N / m, and the rubber roller (Shore A65 degrees) is used for two reciprocating pre-pressing cycles at 0.8MPa. The hot press mold is preheated to 140℃, pressurized to 9MPa at 3MPa / s, held for 280s, and then depressurized at 1.5MPa / s. Gradient cooling: 90℃ / 45s (pressure plate 0.15MPa) → 50℃ / 60s (pressure plate 0.15MPa) → 23℃ / 90s. CNC vibratory knife cutting (vacuum adsorption -0.07MPa, 25000 times / min, 1.5m / min) is used, with a R0.8mm chamfer. The product was tested and found to have an odor level of 6.5, a TVOC of 38 μg / m³, a peel strength of 2.1 N / mm, a flexural strength of 95 MPa, a load capacity of 220 N, a flatness of 0.15 mm, a dimensional accuracy of ±0.2 mm, and an appearance pass rate of 98.5%.
[0079] Example 2:
[0080] Low-odor white paper core with a density of 135 g / m² was selected. The cutting blade speed was 900 r / min, the feed speed was 0.6 m / min, and burrs were removed with 500-grit sandpaper. The flatness correction parameters were 0.35 MPa / 85℃ / 12 s, followed by 4.5 h of static equilibration. PVA white latex was stirred at 250 r / min for 16 min, vacuum degassing was performed at -0.08 MPa / 7 min, the coating amount on the micro-concave roller was 130 g / m², the wet film thickness was 0.13 mm, the coating speed was 2.5 m / min, and after correction, it was allowed to stand for 7 min. The glass fiber surface material was wiped twice with anhydrous ethanol and then treated with plasma (350 W, 25 s, Ar / 70 sccm). After treatment, the water contact angle was 45°, and the dyne pen pressure was 40 mN / m. The edge deviation during lamination was ±0.4 mm, the clamping force was 50 N / m, and the rubber roller was pre-pressed once at 0.6 MPa. The hot press mold is preheated to 150℃, pressurized to 10MPa at 2.5MPa / s, held for 300s, and then depressurized at 1.2MPa / s. Gradient cooling: 85℃ / 50s (pressure plate 0.12MPa) → 55℃ / 55s (pressure plate 0.12MPa) → 23℃ / 80s. CNC milling (vacuum adsorption -0.08MPa, 10000r / min, 1.2m / min) is used for cutting, with a chamfer radius of 0.6mm. The product is tested and found to have an odor level of 6.5, TVOC of 35μg / m³, peel strength of 2.3N / mm, flexural strength of 102MPa, load capacity of 235N, flatness of 0.12mm, dimensional accuracy of ±0.2mm, and an appearance pass rate of 99.0%.
[0081] Comparative Example 1: (Traditional Craftsmanship)
[0082] Traditional honeycomb paper core (formed by bonding and pressing multiple layers of corrugated paper with PUR adhesive) is used as the middle core layer, and burrs are removed after cutting. PUR adhesive is used as the adhesive, with a coating amount of 150g / m², and no degassing occurs after stirring. The glass fiber surface material is only cleaned by wiping with ethanol and is not subjected to plasma or corona surface activation treatment. During lamination, alignment is done manually by visual inspection, with an edge alignment deviation of approximately ±2.0mm, without positioning jigs or pre-pressing. The hot press mold is preheated to 160℃, pressurized to 8MPa, and held for 250s. After holding the pressure, the mold is opened directly to remove the part. The semi-finished product is placed in a room temperature environment for a single cooling of approximately 300s, without gradient cooling or pressure plate constraints. Cutting is done manually with hand-held electric shears, without vacuum adsorption fixation. Testing revealed that the product had an odor rating of 4.0, TVOC of 120 μg / m³, peel strength of 1.6 N / mm, flexural strength of 78 MPa, load capacity of 165 N, flatness of 0.45 mm, dimensional accuracy of ±1.0 mm, and an appearance pass rate of 85.0%. The product had a pungent odor, high VOC emissions, and noticeable bubbles and edge warping on the surface, failing to meet the technical requirements for low-odor automotive interior materials.
[0083] Testing items Example 1 (Invention) Comparative Example 1 (Traditional Process) Odor rating (PV3900, 80℃ / 2h) Level 6.5 Level 4.0 TVOC emissions 38μg / m³ 120μg / m³ Peel strength 2.1 N / mm 1.6N / mm Bending strength 95MPa 78MPa Load performance 220N 165N Flatness (warping) 0.15mm 0.45mm Dimensional accuracy ±0.2mm ±1.0mm diagonal deviation ≤0.5mm Approximately 1.8mm Interlayer bubbles (diameter > 2 mm) none On average, there are 5 to 8 spots per item. Appearance pass rate 98.5% 85.0% Water absorption rate (23℃ / 24h) 3.2% 9.5% Peel strength after heat aging (80℃ / 240h) 2.0 N / mm 1.0 N / mm
[0084] Comparative Example 1 product had a pungent odor and a VOC release of up to 120 μg / m³, more than three times that of Example 1, completely failing to meet the technical requirements for low-odor automotive interiors (odor level ≥ 6, TVOC ≤ 50 μg / m³). Its mechanical properties were comprehensively deteriorated, with peel strength, flexural strength, and load-bearing capacity decreasing by approximately 24%, 18%, and 25%, respectively. Furthermore, after heat aging, the peel strength decreased by up to 50%, resulting in poor interface reliability. Flatness (0.45 mm) and dimensional accuracy (±1.0 mm) were both severely out of tolerance, with obvious bubbles and edge warping on the surface, resulting in an appearance pass rate of only 85.0%. All indicators were comprehensively and significantly deteriorated compared to Example 1, and these disadvantages were compounded and exacerbated by each other in multiple processes.
[0085] The degradation in Comparative Example 1 is the result of the combined defects of the material system and the processing method, which can be attributed to the following four aspects:
[0086] Firstly, VOCs are released at the source of the materials: the honeycomb paper core is made of multiple layers of corrugated paper bonded and pressed with PUR glue. The volatile organic compounds remaining in the PUR glue and the paper itself are released a second time during the hot pressing process at 160℃, which is the root cause of the odor level of 4.0 and TVOC of 120μg / m³. In addition, PUR glue contains isocyanate substances, which are not environmentally friendly.
[0087] Secondly, the interface bonding is inherently weak: the glass fiber surface layer is not activated, has low surface energy and poor wettability (water contact angle of about 78°). Although PUR adhesive has a certain chemical affinity for glass fiber, the bonding node area between the honeycomb core and the surface layer is limited. When subjected to external force, the core layer nodes are prone to detachment, forming a chain failure of "weak interface - delamination - decreased stiffness". Manual visual alignment (±2.0mm) causes local missing adhesive at the edges, further weakening the effective bonding area.
[0088] Third, stress runaway leads to deformation: there is no gradient cooling after hot pressing, the surface of the semi-finished product is rapidly cooled while the core layer is still in a high-temperature viscoelastic state, and the asynchronous shrinkage of the inside and outside generates large internal stress; at the same time, the anisotropy of the honeycomb core is obvious and the thermal expansion is uneven, which manifests as severe warping (0.45mm) and subsequent rebound after stress release; and the substrate internal stress was not eliminated by static balancing before cutting, and the deformation further accumulates.
[0089] Fourth, the molding and cutting precision is out of control: the stacking has no clamping limit and no pre-compression to remove bubbles. The residual bubbles between the layers expand under hot and high temperature to form hollows; the manual electric scissors cutting has no vacuum adsorption fixation. The blank slips during the cutting process, resulting in a dimensional accuracy of ±1.0mm and a diagonal deviation of about 1.8mm, which makes it impossible to assemble and adapt with the spare tire compartment of the vehicle body.
[0090] Comparative Example 2: Using a traditional honeycomb paper core (the rest of the process is the same as in Example 1)
[0091] The low-odor white paper core was replaced with a traditional honeycomb paper core (multi-layer corrugated paper bonded and pressed with PUR glue). The adhesive, activation treatment, lamination, hot pressing, cooling, and cutting parameters were the same as in Example 1.
[0092] Testing items Example 1 Comparative Example 2 Odor rating (PV3900, 80℃ / 2h) Level 6.5 Level 5.0 TVOC emissions 38μg / m³ 72μg / m³ Peel strength 2.1 N / mm 1.8N / mm Bending strength 95MPa 82MPa Load performance 220N 185N flatness 0.15mm 0.22mm Water absorption rate (23℃ / 24h) 3.2% 8.6%
[0093] The honeycomb paper core is made of multiple layers of corrugated paper bonded and pressed with PUR adhesive. The volatile organic compounds remaining in the PUR adhesive and the paper itself are released a second time during the hot pressing (140°C) process, resulting in a 1.5-level decrease in odor level and an increase of about 89% in TVOC. The honeycomb structure has limited bonding points and low node strength, and is prone to core layer node debonding under load, resulting in a significant decrease in bending strength and load performance. The honeycomb core has high porosity and the paper has strong hygroscopicity, with a water absorption rate nearly 2.7 times that of the comparative example, and the load performance deteriorates faster during long-term service.
[0094] The low-odor white paper core is made from virgin wood pulp and treated with a special low-odor process, resulting in extremely low VOC residue. Its continuous sheet structure allows for uniform coating of environmentally friendly adhesives and a large bonding area. When under stress, stress can be continuously transferred through the adhesive layer, thus providing higher rigidity.
[0095] Comparative Example 3: PUR adhesive was used (the white paper core remained the same, and everything else was the same as in Example 1).
[0096] Retain the low-odor white paper core, and replace the starch glue with traditional PUR glue (coating amount is the same at 110g / m²). 2 ).
[0097] Testing items Example 1 Comparative Example 3 Odor rating Level 6.5 Level 5.5 TVOC emissions 38μg / m³ 88μg / m³ Peel strength 2.1 N / mm 2.0 N / mm Bending strength 95MPa 93MPa
[0098] Both have similar mechanical properties (PUR adhesive itself has stronger adhesion), but PUR adhesive has a lower odor level (1 level lower) and a TVOC level (TVOC) level (approximately 1.3 times higher). This indicates that even if a low-odor white paper core is used, if PUR adhesive is still used, the odor and VOC levels will still not meet the standards—one of the main sources of VOCs is adhesives. Starch adhesive / PVA white latex uses water as a dispersion medium, contains no organic solvents or isocyanates, and almost no small molecules escape during hot-pressing curing.
[0099] Comparative Examples 2 and 3 constitute cross-validation of the two variables "substrate" and "adhesive", proving that the combination of "white paper core + environmentally friendly adhesive" in this invention is a necessary condition for odor compliance, and the two have a synergistic relationship. Replacing either one alone is insufficient to solve the problem.
[0100] Comparative Example 4: The glass fiber surface layer was not surface activated (the rest is the same as in Example 1).
[0101] The glass fiber surface material is only wiped with anhydrous ethanol, omitting the plasma treatment process, and the lamination and hot pressing parameters remain unchanged.
[0102] Testing items Example 1 Comparative Example 4 Water contact angle of fiberglass surface 42° 78° Dain pen test 40mN / m through 34mN / m not passing Peel strength 2.1 N / mm 1.2N / mm Peel strength after heat aging (80℃ / 240h) 2.0 N / mm 0.8N / mm Peel strength after damp heat aging (60℃ / 95%RH / 240h) 1.9N / mm 0.6N / mm Layering defect rate (500 samples tested) 0.4% 6.8%
[0103] Unactivated glass fiber has low surface energy and poor wettability (contact angle 78°). Starch adhesive / PVA adhesive is a water-based system, which is difficult to spread and penetrate on low surface energy surfaces, forming a weak boundary layer at the interface, and the peel strength decreases by about 43%. After thermal aging or damp heat aging, the residual stress at the interface and the intrusion of water molecules cause the weak interface to debond, the peel strength decreases to less than 50% of the initial value, and the delamination defect rate increases significantly.
[0104] Plasma treatment introduces polar groups such as hydroxyl and carboxyl groups onto the glass fiber surface through high-energy particle bombardment and generates micro-etching, significantly increasing surface energy. This allows the water-based environmentally friendly adhesive to fully wet and penetrate into the gaps between the glass fiber bundles, forming hydrogen bonds and chemical bonds with the polar groups after curing. It is worth noting that traditional PUR adhesive (Comparative Example 3) contains isocyanate groups, which have a certain chemical affinity for glass fiber, thus achieving acceptable peel strength without activation. However, this invention, precisely because it uses a water-based environmentally friendly adhesive (polar, without active isocyanates), requires activation pretreatment to compensate for interfacial bonding forces.
[0105] Comparative Example 5: Manual visual alignment, no positioning fixtures, no pre-pressing (other aspects are the same as in Example 1).
[0106] The lamination process was changed to manual visual alignment, with an edge alignment deviation of approximately ±2.0mm. Aluminum alloy clamps were not used for limiting, and rubber roller pre-pressing and bubble removal were not performed; the process proceeded directly to hot pressing.
[0107] Testing items Example 1 Comparative Example 5 Interlayer misalignment deviation ±0.3mm ±2.0mm Interlayer bubbles (diameter > 2 mm) none On average, there are 3 to 5 spots per item. Peel strength 2.1 N / mm 1.5N / mm Bending strength 95MPa 84MPa Edge glue shortage / overflow rate after hot pressing 1.2% 9.5% Appearance pass rate 98.5% 88.0%
[0108] Large deviations in manual alignment cause the edges of the white paper core to be misaligned with the edges of the glass fiber, resulting in uneven adhesive layer thickness in some areas—one side of the misaligned area is missing adhesive while the other side is overflowing with adhesive. After hot pressing, the interface bonding at the missing adhesive area is weak, and stress is concentrated at this point when bending, resulting in a decrease in bending strength of about 12%. Residual air bubbles between layers expand under the high temperature of hot pressing, forming hollow defects with a diameter of more than 2mm, which not only affects the appearance but also reduces the effective load-bearing area and decreases the peel strength by about 29%.
[0109] CCD visual alignment (within ±0.5mm) ensures the coaxiality of the three layers, allowing the adhesive layer to flow and spread evenly under pressure; positioning fixtures limit movement on all four sides to prevent slippage during hot pressing; pre-compression removes interlayer air under low pressure to prevent air bubbles from being trapped. These three factors together guarantee "uniform adhesive layer thickness + no air bubbles," which is a prerequisite for consistent bonding strength.
[0110] Comparative Example 6: Single cooling at room temperature (other aspects are the same as in Example 1)
[0111] Gradient cooling is omitted. After hot pressing and depressurization, the semi-finished product is placed directly on a 23°C ambient temperature environment to cool naturally for about 300 seconds without pressure plate constraint.
[0112] Testing items Example 1 (Three-stage gradient cooling) Comparative Example 6 (single cooling at room temperature) Warpage after cooling 0.15mm 0.48mm Dimensional accuracy ±0.2mm ±0.6mm Warpage (springback) after 24 hours of placement 0.18mm 0.52mm Layered defect rate 0.4% 3.2% pass rate 98.5% 90.5%
[0113] The hot-pressed semi-finished product exits the mold at approximately 140℃. When directly exposed to room temperature, the surface rapidly cools and shrinks, while the core layer remains in a high-temperature viscoelastic state. This asynchronous shrinkage between the inner and outer layers generates significant thermal stress. The difference in thermal expansion coefficients between the white paper core and the fiberglass surface further exacerbates stress concentration. After stress release, this manifests as warping deformation (0.48mm, out of tolerance) and subsequent springback (dimensional drift to ±0.6mm). Excessive warping stress can also pull on the interface, inducing micro-delamination.
[0114] The three-stage gradient cooling (90℃→50℃→23℃) controls the cooling rate in segments: the first stage sets the surface gel and gently presses it to prevent warping; the second stage allows the core layer temperature to drop uniformly below vitrification; and the third stage fully releases residual stress at room temperature. The internal and external temperature difference is always kept at a low level, and the thermal stress is "digested" in a gradual process. Therefore, the warping is only about 1 / 3 of the comparative example, and there is no rebound within 24 hours.
[0115] project Example 1 Example 2 Comparative Example 2 (Honeycomb Core) Comparative Example 3 (PUR adhesive) Comparative Example 4 (without activation) Comparative Example 5 (No precise alignment) Comparative Example 6 (Single Cooling) Comparative Example 1 (Traditional Process) Odor rating 6.5 6.5 5.0 5.5 6.5 6.5 6.5 4.0 TVOC (μg / m³) 38 35 72 88 38 38 38 120 Peel strength (N / mm) 2.1 2.3 1.8 2.0 1.2 1.5 2.1 1.6 Bending strength (MPa) 95 102 82 93 92 84 95 78 Load (N) 220 235 185 215 205 195 220 165 Warpage (mm) 0.15 0.12 0.22 0.15 0.16 0.18 0.48 0.45 Dimensional accuracy (mm) ±0.2 ±0.2 ±0.3 ±0.2 ±0.2 ±0.5 ±0.6 ±1.0 Appearance pass rate 98.5% 99.0% 96.0% 97.5% 93.2% 88.0% 90.5% 85.0%
[0116] The above-disclosed embodiments are merely one or more preferred embodiments of this application and should not be construed as limiting the scope of this application. Those skilled in the art can understand that all or part of the processes for implementing the above embodiments and equivalent changes made in accordance with the claims of this application still fall within the scope of this application.
Claims
1. A method for preparing a novel material for a spare tire cover, characterized in that, Includes the following steps: The low-odor white paper core is cut to the designed size, and the cut white paper core is subjected to flatness correction treatment to obtain the pretreated white paper core substrate. An environmentally friendly adhesive is uniformly coated on the upper and lower surfaces of the pretreated white paper core substrate; The glass fiber surface material undergoes surface activation pretreatment. The white paper core substrate coated with environmentally friendly adhesive is precisely aligned and laminated with the upper and lower glass fiber surface materials to form a composite blank; The composite blank is placed in a hot press mold for hot pressing composite molding. The hot pressing temperature, pressure and holding time are controlled to ensure that the layers are firmly bonded to obtain a semi-finished product. The semi-finished product undergoes gradient cooling and shaping treatment; After cooling and shaping, the semi-finished product is precisely cut and trimmed to remove excess edges and corners, forming a prototype spare tire cover that meets product specifications. The prototype spare tire cover is subjected to odor testing and appearance quality inspection. Once it passes the inspection, the finished spare tire cover is obtained.
2. The method for preparing the novel spare tire cover material as described in claim 1, characterized in that, The process of "cutting low-odor white paper cores to the designed dimensions and performing flatness correction on the cut white paper cores to obtain pretreated white paper core substrates" includes the following steps: Unroll the low-odor white paper core roll and cut it to the designed dimensions; Deburr and clean the edges of the cut white paper core; The flatness of the white paper core is tested, and any parts with excessive flatness are corrected. The corrected white paper core is left to stand and balance to eliminate internal stress, thus obtaining the pretreated white paper core substrate.
3. The method for preparing the novel spare tire cover material as described in claim 1, characterized in that, The step of "uniformly coating the upper and lower surfaces of the pretreated white paper core substrate with an environmentally friendly adhesive" includes the following steps: Stir the environmentally friendly adhesive thoroughly and remove any bubbles; An environmentally friendly adhesive is uniformly coated on the upper and lower surfaces of the white paper core substrate using roller coating, scraping, or spraying methods. The coating uniformity is checked, and areas with insufficient or excessive coating are corrected to obtain the coated white paper core substrate.
4. The method for preparing the novel spare tire cover material as described in claim 1, characterized in that, The "surface activation pretreatment of glass fiber surface material" includes the following steps: Clean the surface of the fiberglass material to remove dust, oil, and mold release agent residue; The surface of the glass fiber surface material to be laminated is activated by plasma treatment or corona treatment. To test the surface activation effect, qualified glass fiber surface material was temporarily stored in a clean environment to obtain pretreated glass fiber surface material.
5. The method for preparing the novel spare tire cover material as described in claim 1, characterized in that, The process of "precisely aligning and laminating the white paper core substrate coated with environmentally friendly adhesive with the upper and lower glass fiber surface materials to form a composite preform" includes the following steps: Lay the lower layer of glass fiber surface material flat on the workbench with the surface-activated side facing up. Place the coated white paper core substrate on top of the lower glass fiber surface material; The upper glass fiber surface material is placed over the white paper core substrate, with the surface-activated side facing down. The three layers of material are fixed and pre-pressed using a positioning fixture to remove air bubbles between the layers, resulting in a composite blank.
6. The method for preparing the novel spare tire cover material as described in claim 1, characterized in that, The process of "placing the composite blank in a hot press mold for hot pressing composite molding, controlling the hot pressing temperature, pressure and holding time to ensure that each layer is firmly bonded, and obtaining a semi-finished product" includes the following steps: The composite blank is placed in the preheated hot press mold cavity; The mold is closed and pressure is applied. The environmentally friendly adhesive is then fully cured under specified temperature and pressure conditions. After the pressure holding period is over, slowly release the pressure, open the mold, and remove the semi-finished product.
7. The method for preparing the novel spare tire cover material as described in claim 1, characterized in that, The process of "gradient cooling and shaping of semi-finished products" includes the following steps: The semi-finished product is transferred to the first cooling station for the first stage of cooling, so that the surface temperature is initially reduced. The semi-finished product is transferred to the second cooling station for a second stage of cooling, which further reduces the internal temperature evenly. The semi-finished product is transferred to a room temperature environment for the third stage of cooling and shaping to obtain the cooled and shaped semi-finished product.
